Output performance evaluation of the automatic voltage regulator system on pre-filter control technique - Chibuike Peter Ohanu; Kenneth Chinonso Odo; Luke Uwakwe Omeje; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Automatic voltage regulator (AVR) is used at each generating station or synchronous generators to maintain voltage supply at steady state or at a constant value otherwise the performance of the generator will be affected. The combination of AVR system with controllers clears fluctuation due to variation in load, speed, temperature, and power factor. This causes deviation in generator’s voltage and damage to power equipment. This work presents performance enhancement of AVR system using Proportional Integral and Derivative (PID) with pre-filter control technique. The enhanced performance was achieved by designing a nonlinear model of a synchronous generator, a PID controller and a low pass filter or pre-filter using MATLAB/Simulink model. The introduction of the proposed PID controller with LPF at load variation of 20 seconds, reduces the rise time and the peak time to 5.2975 seconds and 12.31 seconds respectively. This increases the overshoot and the settling time to 4.28 seconds and 17.60 seconds. However, the developed scheme provides a stable time response performance for various desired generator voltages considered. The performance of the proposed scheme was compared with conventional PID controlled AVR system without LPF. The proposed scheme provides more stability as indicated by the percentage overshoot, which is 4.5788% (for PID) and 4.2765% (for PID with prefilter). This has contributed to knowledge an AVR control system with better performance in terms of rise time, peak time, overshoot and settling time for stabilized generator output voltage.